Metabolomics revealed mechanism for the synergistic effect of sulbactam, polymyxin-B and amikacin combination against Acinetobacter baumannii - Zhu, Shixing; Yue, Jiali; Wang, Xintong; Zhang, Jiayuan; Yu, Mingming; Zhan, Yuanchao; Zhu, Yuanqi; Sy, Sherwin K. B.; Lv, Zhihua (Frontiers in Microbiology, 2023)
The emergence of multidrug-resistant (MDR) Acinetobacter baumannii prompts clinicians to consider treating these infections with polymyxin combination.Metabolomic analysis was applied to investigate the synergistic effects of polymyxin-B, amikacin and sulbactam combination therapy against MDR A. baumannii harboring OXA-23 and other drug resistant genes. The drug concentrations tested were based on their clinical breakpoints: polymyxin-B (2 mg/L), amikacin (16 mg/L), polymyxin-B/amikacin (2/16 mg/L), and polymyxin-B/amikacin/sulbactam (2/16/4 mg/L). The triple antibiotic combination significantly disrupted levels of metabolites involved in cell outer membrane including fatty acids, glycerophospholipids, nucleotides, amino acids and peptides as early as 15 min after administration. Amikacin and polymyxin-B alone perturbed a large number of metabolites at 15 min and 1 h, respectively, but the changes in metabolites were short-lived lasting for less than 4 h. In contrast, the combination treatment disrupted a large amount of metabolites beyond 4 h.Compared to the double-combination, the addition of sulbactam to polymyxin-B/amikacin combination produce a greater disorder in A. baumannii metabolome that further confer susceptibility of bacteria to the antibiotics. In conclusion, the metabolomic analysis identified mechanisms responsible for the synergistic activities of polymyxin-B/amikacin/sulbactam against MDR A. baumannii.